2022
DOI: 10.1007/s40121-022-00729-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Nirmatrelvir/Ritonavir, Molnupiravir, and Remdesivir in a Real-World Cohort of Outpatients with COVID-19 at High Risk of Progression: The PISA Outpatient Clinic Experience

Abstract: Introduction Different antivirals are available for the treatment of outpatients with COVID-19. Our aim was to describe a real-world experience of outpatient management of COVID-19 subjects at high risk of progression. Methods This prospective observational study conducted in the University Hospital of Pisa (January 2022–July 2022) included consecutive COVID-19 outpatients with at least one risk factor for disease progression. Patients received nirmatrelvir/ritonavir, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 25 publications
5
50
0
Order By: Relevance
“…In a recent retrospective, observational, nationwide propensity-matched analysis comparing outcomes of US veterans 65 years and older with mild-to-moderate COVID-19, the composite primary outcome of admission or death within 30 days of diagnosis was reached less often in those receiving either MOV or NMV-r versus those that received no antiviral, while NMV-r was more effective than MOV in both outcomes [ 22 ]. The composite outcome of death or hospitalization was shown to be lower in NMV-r treated patients than MOV treated subjects in another study, but the difference in the degree of underlying co-morbidity could contribute to the difference [ 23 ]. Viral rebound was also shown to be uncommon for patients treated with both NMV-r and MOV [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent retrospective, observational, nationwide propensity-matched analysis comparing outcomes of US veterans 65 years and older with mild-to-moderate COVID-19, the composite primary outcome of admission or death within 30 days of diagnosis was reached less often in those receiving either MOV or NMV-r versus those that received no antiviral, while NMV-r was more effective than MOV in both outcomes [ 22 ]. The composite outcome of death or hospitalization was shown to be lower in NMV-r treated patients than MOV treated subjects in another study, but the difference in the degree of underlying co-morbidity could contribute to the difference [ 23 ]. Viral rebound was also shown to be uncommon for patients treated with both NMV-r and MOV [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published literature on the efficacy of NMV-r and MOV has focused on the whole population [ 5 , 6 , 21 ]. There have also been studies on selected patient subgroups including all COVID-19 subjects at high risk of progression [ 23 ], elderly populations [ 22 , 25 ], hematology patients [ 26 ] and solid organ transplant recipients [ 27 ]. However, there has not been any dedicated study focusing on patients with chronic respiratory disease, who are prone to developing severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Tiseo et al suggested that the occurrence of death corresponding to COVID-19 was higher with remdesivir than with molnupiravir or nirmatrelvir/ritonavir [ 87 ]. Molnupiravir was found to be well tolerated when COVID-19 treatment was carried out on older patients and those with vaccination and comorbidities [ 88 ].…”
Section: Impact Of Molnupiravir On Sars-cov-2 Variantsmentioning
confidence: 99%
“…A single-center Italian study from Pisa found no significant difference in effectiveness when comparing molnupiravir (98.2%) to nirmatrelvir/ritonavir (99.2%) or 3-day remdesivir (94.9%), although nirmatrelvir/ritonavir proved more efficient at preventing the need for hospitalization when compared to remdesivir [ 107 ].…”
Section: Management Of Covid-19 In Pwhmentioning
confidence: 99%